Pandemic Storytelling - Alber, Jan; Jumpertz, Jessica; Muijnck, Deborah de (Literature and Cultural Studies E-Books Online, Collection 2025., 2025)
This volume offers unique, interdisciplinary perspectives by evaluating, analyzing, and interpreting how the past, the present, and potential futures may be affected by pandemic storytelling. It explores the interplay between various disciplines that explore COVID-19 narratives or study the influence of pandemics on storytelling. The authors invite you to delve into the intricate social, cultural, and political dynamics between anthropocentric societies, human nature, and their implications for an understanding of our interactions with others and environments. Most importantly, this volume initiates insightful conversations, highlighting that in times of crisis the most valuable thing we can hold on to is human connection.